Impaired fin regeneration and angiogenesis in aged zebrafish and turquoise killifish - Örling Johanna; Kosonen Katri; Villman Jenna; Reichard Martin; Paatero Ilkka (COMPANY BIOLOGISTS LTD, 2025)
Impaired wound healing is associated with aging and has significant effects on human health on an individual level, but also on the whole health-care sector. Deficient angiogenesis appears to be involved in the process, but the underlying biology is still poorly understood. This is at least partially being explained by complexity and costs in using mammalian aging models. To understand aging-related vascular biology of impaired wound healing, we used zebrafish and turquoise killifish fin regeneration models. The regeneration of caudal fin after resection was significantly reduced in old individuals in both species. Age-related changes in angiogenesis, vascular density and expression levels of angiogenesis biomarker VEGF-A were observed. Furthermore, the anti-angiogenic drug vascular endothelial growth factor receptor blocking inhibitor SU5416 reduced regeneration, indicating a key role for angiogenesis in the regeneration of aging caudal fin despite aging-related changes in vasculature. Taken together, our data indicate that these fish fin regeneration models are suitable for studying aging-related decline in wound healing and associated alterations in aging vasculature.